Ребят,помогите пожалуйста упростить выражение: 12 + 4 *( 3z-4 ) -( 5z+ 6 ), при z=3⁄4)

Ребят,помогите пожалуйста упростить выражение: 12 + 4 *( 3z-4 ) -( 5z+ 6 ), при z=3⁄4)
Гость
Ответ(ы) на вопрос:
Гость
12+12z-16-5z-6=7z-10 z=3/4 7*2/4-10=3,5-10=6,5
Гость
[latex]12+4* \frac{3}{4}-4*4-5* \frac{3}{4} -6[/latex] [latex]4* 3*\frac{3}{4} = \frac{12}{4} *3=3*3=9[/latex] [latex]5* \frac{3}{4} = \frac{5}{4} *3= 1,25 *3=3,75[/latex] [latex]12+3-4*4-3,75-6=15-16-6-3,75=-4,75=-19/4[/latex] Ответ: -4,75
Не нашли ответ?
Ответить на вопрос
Похожие вопросы